Human cardiomyocytes are more susceptible to irreversible electroporation by pulsed electric field than human esophageal cells. Issue 20 (27th October 2022) - Casciola, Maura; Keck, Devin; Feaster, Tromondae K.; Blinova, Ksenia
Abstract: Pulse electric field‐based (PEF) ablation is a technique whereby short high‐intensity electric fields inducing irreversible electroporation (IRE) are applied to various tissues. Here, we implemented a standardized in vitro model to compare the effects of biphasic symmetrical pulses (100 pulses, 1–10 μs phase duration (d), 10–1000 Hz pulse repetition rate (f)) using two different human cellular models: human‐induced pluripotent stem cell‐derived cardiomyocytes (hiPSC‐CMs) and human esophageal smooth muscle cells (hESMCs) cultured in monolayer format. We report the PEF‐induced irreversibly electroporated cell monolayer areas and the corresponding electric field thresholds (EFTs) for both cardiac and esophageal cultures. Our results suggest marked cell type specificity with EFT estimated to be 2–2.5 times lower in hiPSC‐CMs than in hESMCs when subjected to identical PEF treatments (e.g., 0.90 vs 1.85 kV/cm for the treatment of 100 pulses with d = 5 μs, f = 10 Hz, and 0.65 vs 1.67 kV/cm for the treatment of 100 pulses with d = 10 μs, f = 10 Hz). PEF treatment can result in increased temperature around the stimulating electrodes and lead to unanticipated thermal tissue damage that is proportional to the peak temperature rise and to the duration of the PEF‐induced elevated temperatures. In our study, temperature increases ranged from less than 1°C to as high as 30°C, however, all temperature changes were transient and quickly returned to baseline and the highest observed ∆T returned to 50% of its maximum recorded temperature in tens of seconds. Abstract : Esophageal fistula is a rare, but life‐threatening risk associated with traditional thermal cardiac ablation procedure in atrial fibrillation patients. Irreversible electroporation (IRE) is a new approach to induce tissue ablation used by novel pulsed electric field (PEF) devices that has demonstrated some tissue specificity in animal models. Here, for the first time, we demonstrate that the electroporation thresholds are lower for human cardiomyocytes than for human esophageal cells for a range of PEF parameters using a well‐controlled in vitro assay. This result may support and improve understanding or the potential superior safety of the IRE‐based cardiac ablation devices.